Pengaruh Disiplin Kerja, Motivasi Kerja, dan Kepuasan Kerja terhadap Kinerja Guru (Studi pada SMK Kartika X-2 Jakarta Selatan) - Herlina Ayu Ningsih; Koen Hendrawan (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the effect of work discipline, work motivation, and job satisfaction on the performance of teachers at SMK Kartika X-2 South Jakarta. The research method used is descriptive quantitative, with data analysis using multiple linear regression. The sampling technique employed is non-probability sampling, specifically saturated sampling, with 45 teacher respondents. Data was collected through questionnaires using a Likert scale and processed using Microsoft Excel software and SPSS version 22. This study focuses on three main variables: work discipline, work motivation, and job satisfaction, which are believed to affect teacher performance. The results of the study indicate that the work discipline variable has a significant effect on teacher performance, meaning that the better the work discipline of teachers, the higher the performance they produce. However, work motivation and job satisfaction were found not to have a significant effect on teacher performance at SMK Kartika X-2 South Jakarta. This finding suggests that work discipline is more dominant in influencing teacher performance compared to work motivation and job satisfaction. The results of this study are expected to provide managerial implications for the school in designing policies to improve teachers' work discipline, which in turn will contribute to the overall improvement of performance within the educational environment of SMK Kartika X-2 South Jakarta.